Oxazolone-Induced Colitis in BALB/C Mice: a New Method to Evaluate the Efficacy of Therapeutic Agents for Ulcerative Colitis - Ryotaro Kojima; Satoko Kuroda; Tomiko Ohkishi; Koichi Nakamaru; Shigeki Hatakeyama (Elsevier, 2004)
A number of experimental models of colitis have been proposed. However, few studies have presented T helper-2 (Th-2) type colitis models that substitute for human ulcerative colitis (UC). In recent years, the murine oxazolone (OXA)-induced colitis model came to be accepted as a Th-2 type model, but it has yet to be used in any pharmacological study. In the present study, we modified the OXA-induced colitis model in BALB/C mice to evaluate the efficacy of treatments for UC. Colitis was induced by intrarectal administration of OXA solution (7.5 mg/mL in 40% ethanol) in a BALB/C strain that is known to favor Th-2 immune responses. A lower mortality rate was obtained in the BALB/C strain than was found in the original method. Histological examination showed that there were morphological similarities to human UC. Increased mRNA expression of interleukin-13, a Th-2 cytokine, was observed in mesenteric lymph nodes. Intrarectal administration of 5-aminosalicylic acid or sodium prednisolone phosphate resulted in a significant improvement in the colitis. These results suggest that the OXA-induced colitis model in the BALB/C strain provides a new way to evaluate the efficacy of therapeutic agents for UC. Keywords:: ulcerative colitis, experimental model, mouse, oxazolone, 5-aminosalicylic acid